Preparation method and application of a multi-pole region disc-shaped sintered neodymium-iron-boron composite magnet
Patent Information
- Application Number
- CN202611386739.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-13
AI Technical Summary
该方式虽可实现各区域磁性的差异化,但相邻磁体之间的拼接界面为胶接或机械结合,结合强度远低于磁体基体,在大型机械装置的振动、离心力及冷热循环工况下,胶层易老化开裂、界面易松脱错位,甚至发生磁环脱落,存在严重的可靠性隐患
由上述实施例可知,本公开制备得到了一种界面结合能力强、磁状态稳定的烧结复合磁体。
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of magnet manufacturing technology, specifically to a method for preparing and applying a multi-polarity disk-shaped sintered NdFeB composite magnet. Background Technology
[0002] In mechanical devices such as magnetic encoders, Hall effect sensors for positioning, and rotational state detection, multiple magnetic pole regions are often formed on the surface of a disc-shaped magnet. The differences in polarity and magnetic field strength of each pole region are used to provide position or status signals to the sensor. Especially in large mechanical devices, the disc-shaped magnet is large in size and needs to withstand complex operating conditions such as vibration, centrifugal force, and thermal cycling for a long time, which places high demands on the structural reliability and magnetic stability of the magnet.
[0003] In existing technologies, such multi-pole disk magnets are mainly obtained through the following methods. First, a single-component magnet blank is sintered and then magnetized in different directions to different regions, resulting in a magnet with multiple magnetic pole regions. However, the remanence of each region in a single-component magnet is the same, and after saturation magnetization, the surface magnetic field strength of each magnetic pole region is basically the same. It is impossible to achieve magnetic pole regions with the same polarity but different magnetic field strengths on the same disk surface, making it difficult to meet the needs of some devices for differentiated magnetic field signals. If a magnetizing magnetic field below saturation is applied to a local area to obtain a weak magnetic region, the magnetization of the magnet in that region is in an unstable state, and demagnetization drift is prone to occur during long-term use and temperature changes. The magnetic field strength in the weak magnetic region cannot remain constant, resulting in poor signal reliability. Second, multiple magnetic blocks or rings with different magnetic properties are pressed, sintered, and magnetized separately, and then concentrically assembled into a multi-pole disk magnet by adhesive bonding or mechanical embedding. While this method can achieve differentiation in the magnetism of different regions, the splicing interface between adjacent magnets is glued or mechanically bonded, and the bonding strength is much lower than that of the magnet substrate. Under the vibration, centrifugal force and hot and cold cycling conditions of large mechanical devices, the glue layer is prone to aging and cracking, the interface is prone to loosening and misalignment, and even the magnetic ring may fall off, posing a serious reliability hazard.
[0004] Therefore, how to achieve differentiated magnetic field strength design for each magnetic pole region on the same disk-shaped magnet, while ensuring a strong bond between the regions and long-term stability of the magnetic state, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] The purpose of this disclosure is to provide a method for preparing and applying a multi-polarity disk-shaped sintered NdFeB composite magnet, in order to address the shortcomings in related technologies.
[0006] 11. According to a first aspect of the present disclosure, a method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet is provided, comprising the following steps: Step 1: Provide a first magnetic powder, a second magnetic powder, and a third magnetic powder; the first magnetic powder, the second magnetic powder, and the third magnetic powder are all made of Nd2Fe. 14 Neodymium iron boron magnetic powder with type B compound as the main phase; the total rare earth mass content of the second magnetic powder is higher than that of the first magnetic powder, and the total rare earth mass content of the first magnetic powder is higher than that of the third magnetic powder; the first magnetic powder and the second magnetic powder also contain Dy and / or Tb, and the total mass content of Dy and / or Tb in the second magnetic powder is higher than that in the first magnetic powder, and the third magnetic powder does not contain Dy or Tb; Step 2: The first magnetic powder, the second magnetic powder, and the third magnetic powder are respectively loaded into the central cylindrical cavity, the middle annular cavity, and the outer annular cavity of the concentric assembly mold, and the adjacent cavities are separated by removable partitions. Step 3: Remove the removable spacer and press the magnetic powder into shape under the orientation magnetic field to obtain a disc-shaped green blank with three concentric zones. Step 4: The disc-shaped green blank is co-sintered under vacuum conditions to metallurgically bond the three zones together at the adjacent interfaces to obtain a disc-shaped sintered magnet blank. Step 5: Perform axial magnetization on the disk-shaped sintered magnet blank in sections, so that the central cylindrical region has N poles, the middle annular region and the outer annular region have S poles, and the surface magnetic induction intensity of the middle annular region is lower than that of the central cylindrical region and the outer annular region, to obtain the multi-pole disk-shaped sintered NdFeB composite magnet.
[0007] In one aspect of the present disclosure, the total rare earth mass content of the first magnetic powder is 31.5%-33.0%, the total rare earth mass content of the second magnetic powder is 34.0%-38.0%, and the total rare earth mass content of the third magnetic powder is 28.5%-31.0%.
[0008] In one aspect of the present disclosure, the total mass content of Dy and Tb in the first magnetic powder is 0.3%-1.5%, and the total mass content of Dy and Tb in the second magnetic powder is 1.8%-3.0%.
[0009] In one aspect of this disclosure, the second magnetic powder further contains Ce, which replaces a portion of Nd, and the mass content of Ce is not greater than 10%.
[0010] In one aspect of the present disclosure, the average particle size of the first magnetic powder, the second magnetic powder, and the third magnetic powder is independently 2.0-5.0 μm; by adjusting the average particle size of the three magnetic powders, the difference between each pair of free sintering line shrinkage rates parallel to the orientation direction and the difference between each pair of free sintering line shrinkage rates perpendicular to the orientation direction at the sintering temperature in step 4 is not greater than 0.5%.
[0011] In one aspect of this disclosure, step 5, the axial magnetization of the partitions, includes: firstly, applying a first-direction pulsed magnetization magnetic field to the entire disk-shaped sintered magnet blank, so that the central cylindrical region, the intermediate annular region, and the outer annular region are all magnetized and exhibit an S pole, wherein the peak value of the first-direction pulsed magnetization magnetic field is 3.5-5.0 MA / m; then, applying a second-direction pulsed magnetization magnetic field opposite to the first direction to a local portion of the central cylindrical region through a cylindrical magnetic pole head, so that the central cylindrical region is flipped and magnetized and exhibits an N pole, wherein the peak value of the second-direction pulsed magnetization magnetic field is 2.8-4.0 MA / m; the outer diameter of the cylindrical magnetic pole head is 2-6 mm smaller than the diameter of the central cylindrical region, and the magnetic field strength leaking from the edge of the cylindrical magnetic pole head to the intermediate annular region is lower than the intrinsic coercivity of the intermediate annular region.
[0012] In one aspect of this disclosure, during pressing in step 3, the orientation magnetic field only covers the central cylindrical cavity and the outer annular cavity, and the intermediate annular cavity is located in the weak magnetic field loop region of the orientation magnetic field, so that the orientation degree of the resulting intermediate annular region is lower than that of the central cylindrical region and the outer annular region.
[0013] In one aspect of the embodiments of this disclosure, the magnetic field strength of the orientation magnetic field in step 3 is not less than 1.2T, the pressing pressure is 100-300MPa, and the pressing method is bidirectional molding or cold isostatic pressing; furthermore, steps 2 and 3 are carried out in an inert atmosphere with an oxygen content of less than 1000ppm, the thickness of the pullable spacer is 0.3-1.0mm, and the surface of the pullable spacer is coated with a boron nitride release layer.
[0014] In one aspect of this disclosure, the primary co-sintering process in step 4 includes: [the process is carried out under a vacuum degree not exceeding 1×10⁻⁶]. -2 Under the condition of Pa, the temperature is increased to 1040-1080℃ at a rate of 3-8℃ / min and held for 3-5h. After the holding period, a two-stage tempering treatment is performed: first, the temperature is held at 880-920℃ for 1-3h, and then at 460-540℃ for 2-5h.
[0015] According to a second aspect of the present disclosure, a multi-pole region disk-shaped composite magnet is provided, which is prepared by the aforementioned preparation method.
[0016] The technical solutions provided by the embodiments of this disclosure may include the following beneficial effects: As can be seen from the above embodiments, this disclosure has prepared a sintered composite magnet with strong interfacial bonding ability and stable magnetic state.
[0017] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Detailed Implementation
[0018] Exemplary embodiments will now be described in detail. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this disclosure. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this disclosure as detailed in the appended claims.
[0019] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. The embodiments described herein are illustrative in nature and are used to provide a basic understanding of this application. The embodiments of this application should not be construed as limiting this application.
[0020] For the sake of brevity, this article only discloses a few specific numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.
[0021] In this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0022] In this description, unless otherwise stated, "above" and "below" include the stated number.
[0023] Unless otherwise stated, the terms used in this disclosure have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the values of the parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this disclosure).
[0024] The term "about" is used to describe and indicate small variations. When used in conjunction with an event or situation, the term may refer to examples in which the event or situation occurred precisely or in examples in which the event or situation occurred very approximately. For example, when used in conjunction with numerical values, the term may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. Additionally, quantities, ratios, and other numerical values are sometimes presented in range format herein. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only numerical values explicitly specified as range limits but also all individual numerical values or subranges covered within the range, as if each numerical value and subrange were explicitly specified.
[0025] The list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0026] The present disclosure will be further described below by way of specific embodiments. Unless otherwise specified, all chemical reagents used in the embodiments of the present disclosure are obtained through conventional commercial means. Unless otherwise specified, all contents mentioned below are mass contents. Unless otherwise specified, it is understood that the process is carried out at room temperature. Example
[0027] Example 1
[0028] In this embodiment, a multi-polar region disk-shaped sintered NdFeB composite magnet with an outer diameter of 200 mm and a thickness of 18 mm is prepared. The diameter of the central cylindrical region is 60 mm, the inner diameter of the middle annular region is 60 mm and the outer diameter is 120 mm, and the inner diameter of the outer annular region is 120 mm and the outer diameter is 200 mm.
[0029] Example 1 includes the following steps: 1. Preparation of magnetic powder: Preparation of the first magnetic powder: The raw materials were prepared according to the following mass percentages: Nd 24.5%, Pr 7.0%, Dy 0.8%, B 0.98%, Co 1.0%, Al 0.15%, Cu 0.12%, Ga 0.10%, with the balance being Fe (total rare earth mass content 32.3%, with 1.5% smelting loss included in the rare earth raw materials); alloy sheets with a thickness of 0.2-0.4 mm were produced by vacuum induction melting combined with thin strip casting; the alloy sheets were placed in a hydrogen treatment device and subjected to hydrogen absorption and dehydrogenation at room temperature under a 500 kPa hydrogen atmosphere, which embrittled the alloy sheets, resulting in coarse powder with a particle size of approximately 0.15-0.2 mm; 0.05 wt% zinc stearate was added to the coarse powder as a pulverizing aid, and after uniform mixing, it was pulverized by an air jet mill. The average particle size was measured to be 3.0 μm by laser diffraction, thus obtaining the first magnetic powder.
[0030] Preparation of the second magnetic powder: The raw materials were prepared according to the following mass percentages: Nd 27.0%, Pr 6.5%, Dy 2.0%, B 0.95%, Co 0.5%, Al 0.10%, Cu 0.15%, Ga 0.10%, with the balance being Fe (total rare earth content 35.5%). The second magnetic powder was obtained by using the same strip casting, hydrogen crushing, and air jet milling processes as the first magnetic powder, and was pulverized to an average particle size of 3.6 μm. Because the second magnetic powder has a high total rare earth content, a large amount of sintering liquid phase, and a greater tendency to shrink, its average particle size was controlled to be coarser than that of the first and third magnetic powders to compensate for sintering shrinkage.
[0031] Preparation of the third magnetic powder: The raw materials were prepared according to the following mass percentages: Nd 25.0%, Pr 6.0%, B 1.00%, Co 0.9%, Al 0.20%, Cu 0.10%, with the balance being Fe (total rare earth mass content is 31.0%, excluding Dy and Tb). The third magnetic powder was obtained by using the same strip casting, hydrogen crushing and air jet milling process as the first magnetic powder to pulverize it to an average particle size of 2.9 μm.
[0032] Three types of magnetic powder were individually pressed into oriented discs with a diameter of 10 mm and a thickness of 7 mm under an orientation magnetic field of 1.8 T. These discs were then vacuum sintered at 1060℃ for 4 h and subjected to a two-stage tempering process of 900℃×2 h + 500℃×3 h, yielding samples one, two, and three corresponding to the first, second, and third magnetic powders, respectively. Testing revealed the following: Sample 1 had a remanence Br of 1.33 T and an intrinsic coercivity Hcj of 1420 kA / m; Sample 2 had a remanence Br of 0.90 T and an intrinsic coercivity Hcj of 2100 kA / m; and Sample 3 had a remanence Br of 1.43 T and an intrinsic coercivity Hcj of 1080 kA / m. The remanence of the second sample is 0.68 compared to that of the first sample, and 0.63 compared to that of the third sample; the intrinsic coercivity of the second sample is 1.48 compared to that of the first sample.
[0033] Meanwhile, the free sintering linear shrinkage rates of the three magnetic powders under the condition of 1060℃×4h were measured: parallel to the orientation direction, they were 14.2%, 14.4%, and 14.3%, respectively, and perpendicular to the orientation direction, they were 18.6%, 18.9%, and 18.7%, respectively, with the difference between each pair not exceeding 0.3%.
[0034] 2. Sectionalized fabric: This step is performed in a nitrogen-protected glove box (oxygen content 800ppm). A concentric combination mold is used, with the mold cavity designed to accommodate sintering shrinkage. The cavity consists of a central cylindrical cavity, an intermediate annular cavity, and an outer annular cavity, with adjacent cavities separated by stainless steel spacers with a 0.5mm thick boron nitride release coating. Approximately 385g of the first magnetic powder is weighed and placed into the central cylindrical cavity, approximately 1155g of the second magnetic powder is weighed and placed into the intermediate annular cavity, and approximately 2735g of the third magnetic powder is weighed and placed into the outer annular cavity. After spreading the powder, it is smoothed.
[0035] 3. Magnetic field orientation pressing molding: Remove the stainless steel spacer and place the mold in the orientation magnetic field device for bidirectional molding: the magnetic field strength of the orientation magnetic field is 1.8T and the pressing pressure is 200MPa; the orientation yoke only covers the central cylindrical cavity and the outer annular cavity, and the middle annular cavity is located in the weak magnetic field loop of the orientation magnetic field, so that the orientation degree of the middle annular region is lower than that of the central cylindrical region and the outer annular region, resulting in a disc-shaped green blank with three concentric regions.
[0036] 4. Vacuum co-sintering and tempering in one step: The disc-shaped green blank is placed in a vacuum sintering furnace and evacuated to a vacuum degree of 5×10⁻⁶. -3 Pa was heated to 1060℃ at a rate of 5℃ / min and held for 4 hours; then subjected to a two-stage tempering treatment: first held at 900℃ for 2 hours, then held at 500℃ for 3 hours, and cooled with argon gas to obtain a disc-shaped sintered magnet blank. The density of the blank was measured to be 7.52 g / cm³.3 The interface between the two adjacent zones is densely bonded, without cracks, delamination, or misalignment; electron probe line scanning shows that the contents of Nd, Pr, and Dy at the interface are continuously transitioned, with a composition gradient layer width of approximately 120 μm; the interfacial shear strength is 62 MPa.
[0037] 5. Two-step axial magnetization in different zones: Step 1: Place the disc-shaped sintered magnet blank in the solenoid cavity of the pulse magnetizer and apply an axial pulse magnetizing magnetic field with a peak value of 4.5 MA / m to the entire blank, so that the central cylindrical area, the middle annular area and the outer annular area are all saturated magnetized and present the S pole.
[0038] Step 2: Using a cylindrical magnetic pole head with an outer diameter of 56 mm (4 mm smaller than the diameter of the central cylindrical region), an axial pulsed magnetizing magnetic field, opposite to that in Step 1, is applied locally to the central cylindrical region, with a peak value of 3.2 MA / m. This causes the central cylindrical region to flip and magnetize, exhibiting an N pole. Testing revealed that the magnetic field strength leaking from the edge of the magnetic pole head to the inner edge of the central annular region is approximately 350 kA / m, far lower than the intrinsic coercivity of the central annular region (2100 kA / m), indicating that the magnetic state of the central annular region remains undisturbed.
[0039] The surface magnetic induction intensity of the obtained multi-pole disk-shaped sintered NdFeB composite magnet was measured using a gaussmeter: the surface magnetic induction intensity of the central cylindrical region (N pole) was 3240 Gauss, the middle annular region (S pole) was 1460 Gauss, and the outer annular region (S pole) was 2940 Gauss; the surface magnetic induction intensity of the middle annular region was 49.7% of that of the outer annular region; the boundary between the N pole region and the S pole region was clear, and the width of the magnetization transition zone was less than 1 mm.
[0040] The product in this embodiment was subjected to random vibration testing (10-2000Hz, 2 hours) and high and low temperature thermal cycling testing (minus 40℃ to 120℃, 50 cycles). After the tests: the product's appearance was intact, with no cracks or misalignments; the surface magnetic induction intensity change rates of the central cylindrical area, the middle annular area, and the outer annular area were 0.7%, 0.5%, and 0.9%, respectively, all less than 1%.
[0041] Example 2 The steps of Example 2 are basically the same as those of Example 1, except that the nominal composition (mass percentage) of the second magnetic powder is Nd 20.5%, Pr 5.0%, Ce 8.0%, Dy 2.5%, B 0.95%, Co 0.5%, Cu 0.15%, and the balance is Fe (total rare earth mass content is 36.0%, of which Ce mass content is 8.0%), and it is air-milled to an average particle size of 3.7 μm. The remanence of the obtained second sample is 0.86 T, and the intrinsic coercivity Hcj is 2050 kA / m. The ratio of its remanence to that of the first and third samples is 0.65 and 0.60, respectively, and the ratio of its intrinsic coercivity to that of the first sample is 1.44. The free sintering line shrinkage is 14.5% parallel to the orientation direction and 19.0% perpendicular to the orientation direction, and the difference between it and the other two magnetic powders is no greater than 0.4%.
[0042] Testing revealed the following: the surface magnetic induction intensity of the central cylindrical region (N pole) was 3235 Gauss, the middle annular region (S pole) was 1390 Gauss, and the outer annular region (S pole) was 2938 Gauss, with the middle annular region exhibiting 47.3% of the intensity of the outer annular region; the interfacial shear strength was 60 MPa; and the surface magnetic change rates of the three regions after thermal cycling were 0.8%, 0.6%, and 0.9%, respectively. In this embodiment, Ce was used to replace part of the Nd in the second magnetic powder, reducing the cost of rare earth raw materials in the middle region by approximately 15%, while maintaining magnetic properties comparable to those in Example 1. This demonstrates that replacing part of the Nd with Ce within a range not exceeding 10% is a feasible cost-reduction strategy.
[0043] Example 3
[0044] The steps of Example 3 are basically the same as those of Example 1, except that: the nominal composition (mass percentage) of the second magnetic powder is Nd 29.0%, Pr 6.0%, Dy 2.5%, B 0.95%, Co 0.5%, Cu 0.15%, and the balance is Fe (total rare earth mass content is 37.5%); to compensate for its greater sintering shrinkage, the average particle size is controlled at 4.2 μm. The remanence Br of the obtained second sample is 0.84T, the intrinsic coercivity Hcj is 2300 kA / m, the remanence ratios are 0.63 and 0.59, and the coercivity ratio is 1.62; the free sintering linear shrinkage is 14.6% parallel to the orientation direction and 19.1% perpendicular to the orientation direction, which is 0.4% and 0.5% different from the first and third magnetic powders, respectively, and is at the edge of the matching window.
[0045] Testing revealed the following: 3238 Gauss in the central cylindrical region, 1355 Gauss in the middle annular region, and 2935 Gauss in the outer annular region, with the middle annular region exhibiting 46.2% of the strength of the outer annular region; the interfacial shear strength was 55 MPa; and the surface magnetic flux change rates of the three regions after thermal cycling were 0.9%, 0.8%, and 1.0%, respectively. The overall performance of this embodiment is inferior to that of Embodiment 1.
[0046] Example 4
[0047] The steps in Example 4 are basically the same as those in Example 1, except that in step 3, the orientation yoke covers all three cavities: the central cylindrical cavity, the middle annular cavity, and the outer annular cavity. The magnetic powder orientation degree in the three regions is basically the same (i.e., a weak orientation design is not used). Testing showed: 3238 Gauss in the central cylindrical region, 1600 Gauss in the middle annular region, and 2938 Gauss in the outer annular region, with the middle annular region accounting for 54.5% of the outer annular region; the interfacial shear strength was 62 MPa; and the surface magnetic change rates in the three regions after the thermal cycling test were 0.7%, 0.6%, and 0.9%, respectively.
[0048] In this embodiment, the orientation degree of the middle annular region of the product is increased, and its surface magnetic induction intensity increases from 1460 Gauss to 1600 Gauss. The overall performance of this embodiment is inferior to that of Embodiment 1.
[0049] Example 5
[0050] The steps in Example 5 are basically the same as those in Example 1, except that the nominal composition (mass percentage) of the second magnetic powder is Nd 27.5%, Pr 6.5%, Dy 1.2%, B 0.95%, Co 0.5%, Cu 0.15%, and the balance is Fe (total rare earth mass content is 35.2%, Dy mass content is 1.2%). The remanence Br of the obtained second sample is 0.93T, and the intrinsic coercivity Hcj is 1640kA / m. The ratio of its intrinsic coercivity to that of the first sample is 1.15, which is less than 1.3.
[0051] Testing revealed that the initial surface magnetic field was 3240 Gauss in the central cylindrical region, 1505 Gauss in the middle annular region, and 2940 Gauss in the outer annular region. However, after the second step of local reverse magnetization, the change rate of surface magnetic induction intensity in the middle annular region reached 3.2% (compared to only 0.4% in Example 1), and the surface magnetic field of the middle annular region drifted by 1.8% after thermal cycling. This indicates that when the Dy content of the second magnetic powder is less than 1.8%, the coercivity reserve of the middle annular region is insufficient, making it difficult to resist the leakage magnetic field from the local reverse magnetization in the center and long-term thermal disturbances, resulting in a decrease in the magnetic stability of the weak magnetic region.
[0052] Example 6
[0053] The steps of Example 6 are basically the same as those of Example 1, except that the nominal composition (mass percentage) of the first magnetic powder is Nd 24.9%, Pr 7.0%, Dy 0.1%, B 0.98%, Co 1.0%, Al 0.15%, Cu 0.12%, Ga 0.10%, with the balance being Fe (total rare earth mass content is 32.0%, Dy mass content is 0.1%). The remanence Br of the obtained first sample is 1.36T, and the intrinsic coercivity Hcj is 1150kA / m.
[0054] Testing revealed that the initial surface magnetic field was 3270 Gauss in the central cylindrical region, 1460 Gauss in the middle annular region, and 2950 Gauss in the outer annular region, comparable to Example 1. However, after thermal cycling, the surface magnetic field drift in the central cylindrical region reached 2.3% (compared to only 0.7% in Example 1). The central cylindrical region, after exhibiting an N pole, is subjected to the reverse static magnetic field of the S pole regions on both sides for a long period. When the Dy content of the first magnetic powder is below 0.3%, the coercivity reserve in the central region is insufficient, resulting in poor long-term magnetic stability.
[0055] Example 7
[0056] The steps in Example 7 are basically the same as those in Example 1, except that the nominal composition (mass percentage) of the second magnetic powder is Nd 25.2%, Pr 6.5%, Dy 1.8%, B 0.95%, Co 0.5%, Cu 0.15%, and the balance is Fe (total rare earth mass content is 33.5%, which is still higher than the 32.3% of the first magnetic powder, but lower than 34.0%). The remanence of the obtained second sample is 1.06T, the intrinsic coercivity is 1900kA / m, and the ratio of its remanence to that of the first sample is 0.80.
[0057] Testing revealed the following: 3236 Gauss in the central cylindrical region, 2050 Gauss in the middle annular region, and 2936 Gauss in the outer annular region. The middle annular region's Gauss content was 69.8% of that of the outer annular region. The signal differentiation between the weak and strong magnetic regions was severely insufficient, making reliable sensor differentiation difficult. This indicates that when the total rare earth content of the second magnetic powder decreases, the main phase is insufficiently diluted, failing to form an effective weak magnetic region.
[0058] Example 8
[0059] The steps in Example 8 are basically the same as those in Example 1, except that the average particle size of the second magnetic powder is 2.6 μm (without particle size compensation). Its free sintering line shrinkage is 15.6% parallel to the orientation direction and 20.1% perpendicular to the orientation direction. The difference between its shrinkage in the perpendicular direction and that of the first and third magnetic powders is 1.4%, and the difference in the parallel direction is 1.3%. Testing revealed that circumferential microcracks appeared at the interface between the middle and outer annular regions after co-sintering, and the interfacial shear strength was only 28 MPa. After random vibration testing, the cracks propagated and localized spalling occurred, resulting in product scrap.
[0060] Example 9
[0061] The steps in Example 9 are basically the same as those in Example 1, except that steps 2 and 3 are performed in an air atmosphere (without an inert atmosphere). Testing revealed that the magnetic powder underwent surface oxidation during the feeding and pressing process, resulting in a comprehensive decrease in the surface magnetic properties of the three regions of the obtained magnet: 3090 Gauss in the central cylindrical region, 1360 Gauss in the middle annular region, and 2790 Gauss in the outer annular region, a decrease of approximately 4%-5% compared to Example 1; oxide inclusions were present at the interface, with an interfacial shear strength of 35 MPa; after thermal cycling tests, the surface magnetic property changes in the three regions were 1.6%, 1.3%, and 1.8%, respectively. This indicates that the feeding and pressing process of the NdFeB system must be carried out in a low-oxygen inert atmosphere.
[0062] Example 10
[0063] The steps in Example 10 are basically the same as those in Example 1, except that the co-sintering temperature in step 4 is 1010℃ (lower than 1040℃). Testing showed that the density of the blank was only 7.31 g / cm³. 3 The densification was insufficient; the interfacial shear strength was 33 MPa; the surface magnetic properties of the three zones were 3150 Gauss in the central cylindrical zone, 1400 Gauss in the middle annular zone, and 2860 Gauss in the outer annular zone, all of which were too low; after the thermal cycling test, the change rates of surface magnetic properties in the three zones were 1.2%, 1.0%, and 1.4%, respectively. This indicates that when the co-sintering temperature is below 1040℃, the amount of liquid phase is insufficient, and both densification and interfacial metallurgical bonding are inadequate.
[0064] Example 11
[0065] The steps in Example 11 are basically the same as those in Example 1, except that in step 5, the outer diameter of the cylindrical magnetic pole head is 59 mm (only 1 mm smaller than the diameter of the central cylindrical region). Testing revealed that the magnetic field strength leaking from the edge of the magnetic pole head to the inner edge of the central annular region was approximately 780 kA / m. After local reverse magnetization in the second step, the surface magnetic field change rate of the central annular region reached 2.6%, and the magnetization transition zone between the N and S pole regions widened to approximately 3 mm, resulting in unclear pole region boundaries. This indicates that a 2-6 mm smaller outer diameter than the central cylindrical region is a crucial condition for ensuring clear pole region boundaries and preventing leakage magnetic field disturbances in the weak magnetic region.
[0066] Comparative Example 1 The central cylindrical cavity, the intermediate annular cavity, and the outer annular cavity were all filled with the third magnetic powder from Example 1 (i.e., the three regions used the same composition, and there was no gradient in the total rare earth content). The remaining steps were the same as in Example 1. Testing revealed that the central cylindrical region had a magnetic flux density of 3220 Gauss, the intermediate annular region 2890 Gauss, and the outer annular region 2930 Gauss. The surface magnetic induction intensity of the three regions was basically the same, making it impossible to obtain a weakly magnetic intermediate annular region.
[0067] Comparative Example 2 All three regions used the third magnetic powder from Example 1, and disc-shaped sintered magnets were prepared according to the steps in Example 1. During magnetization, after the overall saturation magnetization in the first step, a pulsed magnetic field with a peak value lower than its saturation magnetization field strength was applied to the middle annular region using a ring magnetic pole head for undermagnetization, so that the initial surface magnetic induction intensity of the middle annular region was about 1460 Gauss. After being placed at room temperature for 30 days, the value was measured again as 1620 Gauss (drift +11.0%), and after being kept at 60℃ for 24 hours, the value was measured again as 1710 Gauss (cumulative drift +17.1%). This indicates that the weak magnetic region obtained by undermagnetization is in an unsaturated magnetization state, the magnetic state is unstable, and the surface magnetic induction intensity drifts significantly with time and temperature.
[0068] Comparative Example 3 The first, second, and third magnetic powders from Example 1 were individually molded, sintered, and magnetized to obtain a central cylindrical magnetic block, an intermediate annular magnetic block, and an outer annular magnetic block. These three components were then concentrically bonded together using epoxy adhesive to form a disk with an outer diameter of 200 mm. This bonded disk, along with the product from Example 1, underwent random vibration testing (10-2000 Hz, 2 hours) and high / low temperature thermal cycling testing (-40°C to 120°C, 50 cycles). After the tests: the adhesive layer of the bonded disk in Comparative Example 3 showed visible cracks, the outer annular magnetic block loosened and experienced radial displacement, and the surface magnetic distribution in each area of the disk was significantly abnormal; while the product from Example 1 remained intact, and the change rate of surface magnetic induction intensity in all three areas was less than 1%.
[0069] Comparative Example 4 The intermediate annular cavity was replaced with SmCo5 type magnetic powder (Br = 0.90T, Hcj = 2100kA / m, average particle size 3.6μm). The central cylindrical cavity and the outer annular cavity were still filled with the first and third magnetic powders from Example 1. The remaining steps were the same as in Example 1, and a single co-sintering was attempted. Results: At the NdFeB sintering temperature of 1060℃, the SmCo5 region was not sufficiently densified, and Sm, Nd, Fe, and Co reacted at the interface to form impurity phases, resulting in interface cracking. If the sintering temperature was increased to about 1200℃, which is required for SmCo5, the NdFeB grains grew abnormally, and the remanence and coercivity deteriorated significantly.
[0070] Other embodiments of this disclosure will readily occur to those skilled in the art upon consideration of the specification and practice of the disclosure herein. This disclosure is intended to cover any variations, uses, or adaptations of this disclosure that follow the general principles of this disclosure and include common knowledge or customary techniques in the art not disclosed herein.
Claims
1. A method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet, characterized in that, Includes the following steps: Step 1: Provide a first magnetic powder, a second magnetic powder, and a third magnetic powder; the first magnetic powder, the second magnetic powder, and the third magnetic powder are all made of Nd2Fe. 14 Neodymium iron boron magnetic powder with type B compound as the main phase; the total rare earth mass content of the second magnetic powder is higher than that of the first magnetic powder, and the total rare earth mass content of the first magnetic powder is higher than that of the third magnetic powder; the first magnetic powder and the second magnetic powder also contain Dy and / or Tb, and the total mass content of Dy and / or Tb in the second magnetic powder is higher than that in the first magnetic powder, and the third magnetic powder does not contain Dy or Tb; Step 2: The first magnetic powder, the second magnetic powder, and the third magnetic powder are respectively loaded into the central cylindrical cavity, the middle annular cavity, and the outer annular cavity of the concentric assembly mold, and the adjacent cavities are separated by removable partitions. Step 3: Remove the removable spacer and press the magnetic powder into shape under the orientation magnetic field to obtain a disc-shaped green blank with three concentric zones. Step 4: The disc-shaped green blank is co-sintered under vacuum conditions to metallurgically bond the three zones together at the adjacent interfaces to obtain a disc-shaped sintered magnet blank. Step 5: Perform axial magnetization on the disk-shaped sintered magnet blank in sections, so that the central cylindrical region has N poles, the middle annular region and the outer annular region have S poles, and the surface magnetic induction intensity of the middle annular region is lower than that of the central cylindrical region and the outer annular region, to obtain the multi-pole disk-shaped sintered NdFeB composite magnet.
2. The method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet according to claim 1, characterized in that, The total rare earth content of the first magnetic powder is 31.5%-33.0%, the total rare earth content of the second magnetic powder is 34.0%-38.0%, and the total rare earth content of the third magnetic powder is 28.5%-31.0%.
3. The method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet according to claim 1 or 2, characterized in that, The total mass content of Dy and Tb in the first magnetic powder is 0.3%-1.5%, and the total mass content of Dy and Tb in the second magnetic powder is 1.8%-3.0%.
4. The method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet according to claim 3, characterized in that, The second magnetic powder also contains Ce, which replaces a portion of Nd, and the mass content of Ce is no more than 10%.
5. The method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet according to any one of claims 1-4, characterized in that, The average particle size of the first magnetic powder, the second magnetic powder, and the third magnetic powder is independently 2.0-5.0 μm. By adjusting the average particle size of the three magnetic powders, the difference between each pair of free sintering line shrinkage parallel to the orientation direction and the difference between each pair of free sintering line shrinkage perpendicular to the orientation direction at the sintering temperature in step 4 is not greater than 0.5%.
6. The method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet according to claim 1, characterized in that, Step 5, the axial magnetization of the partitions, includes: firstly, applying a first-direction pulsed magnetization magnetic field to the entire disk-shaped sintered magnet blank, so that the central cylindrical region, the middle annular region, and the outer annular region are all magnetized and exhibit an S pole, with the peak value of the first-direction pulsed magnetization magnetic field being 3.5-5.0 MA / m; then, applying a second-direction pulsed magnetization magnetic field, opposite to the first direction, to a local area of the central cylindrical region through a cylindrical magnetic pole head, so that the central cylindrical region is flipped and magnetized and exhibits an N pole, with the peak value of the second-direction pulsed magnetization magnetic field being 2.8-4.0 MA / m; the outer diameter of the cylindrical magnetic pole head is 2-6 mm smaller than the diameter of the central cylindrical region, and the magnetic field strength leaking from the edge of the cylindrical magnetic pole head to the middle annular region is lower than the intrinsic coercivity of the middle annular region.
7. The method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet according to claim 1, characterized in that, During the pressing process in step 3, the orientation magnetic field only covers the central cylindrical cavity and the outer annular cavity. The intermediate annular cavity is located in the weak magnetic field loop region of the orientation magnetic field, resulting in a lower orientation degree in the intermediate annular region compared to the central cylindrical region and the outer annular region.
8. The method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet according to claim 1, characterized in that, In step 3, the magnetic field strength of the orientation magnetic field is not less than 1.2T, the pressing pressure is 100-300MPa, and the pressing method is bidirectional molding or cold isostatic pressing; furthermore, steps 2 and 3 are carried out in an inert atmosphere with an oxygen content of less than 1000ppm, the thickness of the pullable spacer is 0.3-1.0mm, and the surface of the pullable spacer is coated with a boron nitride release layer.
9. The method for preparing a multi-pole region disk-shaped sintered NdFeB composite magnet according to claim 1, characterized in that, The co-sintering process described in step 4 includes: [the process is carried out under a vacuum degree not exceeding 1×10⁻⁶]. -2 Under the condition of Pa, the temperature is increased to 1040-1080℃ at a rate of 3-8℃ / min and held for 3-5h. After the holding period, a two-stage tempering treatment is performed: first, the temperature is held at 880-920℃ for 1-3h, and then at 460-540℃ for 2-5h.
10. A multi-pole region disk-shaped composite magnet, characterized in that, The multi-pole disk-shaped composite magnet is prepared by the preparation method described in any one of claims 1-9.